If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 + -4x = 2x Solving 7 + -4x = 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 7 + -4x + -2x = 2x + -2x Combine like terms: -4x + -2x = -6x 7 + -6x = 2x + -2x Combine like terms: 2x + -2x = 0 7 + -6x = 0 Add '-7' to each side of the equation. 7 + -7 + -6x = 0 + -7 Combine like terms: 7 + -7 = 0 0 + -6x = 0 + -7 -6x = 0 + -7 Combine like terms: 0 + -7 = -7 -6x = -7 Divide each side by '-6'. x = 1.166666667 Simplifying x = 1.166666667
| 6v-105=25v+18 | | -5(6a-3)= | | -2+-2=1.2p+.25p | | 6a^6-42a^5-108a^4=0 | | c-59=-7 | | 2y=4-2x | | 7(-4m-6)=8m+6(2-3m) | | -19.1=x-1.9+x | | .5(s+9)=39 | | 42x^9-147x^7=0 | | 5b=-15+8b | | 6-(4y+1)=5(y+1)-y | | 6(t-1)=9(r-4) | | 1.6(d+-2)=40 | | y^2-3x-6y=8 | | 15y^2+29y+12= | | 49-54= | | 9x+2(x-1)=11x+8 | | 3(2x-1)+x=-x-3 | | 8k+k-7-10k= | | 3(2x+4)+6=2(x-5) | | 42m=999 | | 4-3x=26 | | 3x^2+17x+8= | | 42m=9999 | | 1000000+100000000000000000000000000000= | | 3(2x+4)+6=2x-5 | | 180=16r^2 | | 15=-9+x | | 9r^3-36r=0 | | =350-14x | | 20=-5y-3x |